The Cambridge companion to Ockham - Spade, Paul Vincent (Cambridge companions to philosophy, 1999)
The Franciscan William of Ockham (c. 1288–1347) was an English medieval philosopher, theologian, and political theorist. Along with Thomas Aquinas and Duns Scotus, he is regarded as one of the three main figures in medieval philosophy after around 1150. Ockham is important not only in the history of philosophy and theology, but also in the development of early modern science and of modern notions of property rights and church-state relations. This volume offers a full discussion of all significant aspects of Ockham's thought: logic, philosophy of language, metaphysics and natural philosophy, epistemology, ethics, action theory, political thought and theology. It is the first study of Ockham in any language to make full use of the new critical editions of his works, and to consider recent discoveries concerning his life, education, and influences.